Perceived Impact of Vocational Skills Acquisition On Reformation and Reduction of Recidivism by Ex-Convicts of Gombe Central Correctional Centre - Inusa,, Diana (Kashere Journal of Education, 2021)
Reformation of prison inmates is one of the most utmost functions of the Nigerian Correctional Service. The main focus of this study was to assess the perceived impact of vocational skills acquisition on reformation and reduction of recidivism by ex-convicts of Gombe Central Correctional Center, Nigeria. The study used 30 ex-convicts who were jailed between six months and eight years. The instrument used for data collection was structured questionnaire which was validated by specialists in measurement and evaluation, and reliability test conducted in the Faculty of Education, University of Maiduguri. Data collected were analysed using descriptive statistics, mean and standard deviation. The findings revealed that most of the ex-convicts were male, with informal education and age range of between 21 and 40 years. The respondents engaged more in carpentry (37%) and Welding (33%). The vocational skills acquired by inmates had great and positive impact on their reformation. The study therefore recommends that: there is need for the Nigeria Correctional Service authorities to introduce more vocational skills acquisition programmes in Gombe Central Correctional Centre; Collaborative provision should be made between the Nigerian Correctional Service (NCS) and other agencies as well as other Vocational and Technical Education (VTE) centres towards promotion of rehabilitation of prison inmates through vocational skills acquisition programme.